2019
DOI: 10.1097/meg.0000000000001379
|View full text |Cite
|
Sign up to set email alerts
|

A randomized double-blinded sham-controlled cross-over trial of tined-lead sacral nerve stimulation testing for chronic constipation

Abstract: ObjectivesSacral nerve stimulation (SNS) may provide long-term symptom relief to patients suffering chronic constipation. Patients are currently selected for SNS using a 2week peripheral nerve evaluation (PNE) comprising stimulation via temporary leads. However, only 40% of test responders receive long-term benefit from treatment meaning that healthcare costs per successfully treated patient are too high. The primary objective was to assess tined-lead testing to predict benefit from SNS for chronic constipatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 26 publications
1
22
0
Order By: Relevance
“…158 Contrary to findings from uncontrolled studies, 159 findings from more rigorous studies [160][161][162] and from a double-blind study of 45 patients with constipation are less encouraging. 163 Sacral nerve stimulation is therefore not recommended for treating refractory constipation. Poor-quality studies found that rectal suspension procedures, a form of rectopexy, might improve symptoms and also be accompanied by healing of prolapse-associated solitary rectal ulcer syndrome in patients with refractory constipation and rectal intussusception.…”
Section: Management Of Chronic Constipation Refractive To Medical Therapymentioning
confidence: 99%
“…158 Contrary to findings from uncontrolled studies, 159 findings from more rigorous studies [160][161][162] and from a double-blind study of 45 patients with constipation are less encouraging. 163 Sacral nerve stimulation is therefore not recommended for treating refractory constipation. Poor-quality studies found that rectal suspension procedures, a form of rectopexy, might improve symptoms and also be accompanied by healing of prolapse-associated solitary rectal ulcer syndrome in patients with refractory constipation and rectal intussusception.…”
Section: Management Of Chronic Constipation Refractive To Medical Therapymentioning
confidence: 99%
“…The long-term outcome of these patients is now available, showing that two of them (both young females, candidates for total colectomy) are still using the SNS with moderate benefits. However, a placebo effect and the willingness to believe in an advanced therapy like SNS could explain these findings [33,34]. The effects of depressive disorders demonstrated by the MMPI questionnaire in the response rate to SNS has also been considered recently, and it has been shown that a minority of constipated patients with normal MMPI could potentially benefit from permanent SNS [32].…”
Section: Discussionmentioning
confidence: 99%
“…SNM was shown to be a beneficial and cost-effective intervention in different subtypes of patients suffering from faecal incontinence refractory to standard treatments in both short- [79,80,86,89,90] and long-term [108,139,140] studies, receiving regulatory approval in most major health systems [95,141]. On the other hand, after being shown to be effective in the treatment of idiopathic slow-and normaltransit constipation resistant to conservative treatment in preliminary studies [75,142], SNM showed no superiority to sham stimulation in controlled trials [97][98][99].…”
Section: Bm For Pelvic Dysfunctionsmentioning
confidence: 99%
“…To date, a positive PNE test remains the sole predictor for the long-term efficacy of SNM [90,131,147]. However, for some diseases, such as chronic constipation, a positive PNE seems not to be a good predictor of success [97][98][99][100], as in other conditions, where still the nonresponder rates after the implantation of a chronic neuromodulator can be as high as 40% [106,133,147]. One reason for this could be the standard unipolar wire electrode itself, which is significantly thinner than the standard permanent quadripolar electrode, leading to a greater risk of electrode dislocation.…”
Section: Bm For Pelvic Dysfunctionsmentioning
confidence: 99%